A RESEARCH ABOUT PAIRED ASSOCIATED FLUCTUATIONS MEMORY - Solís Macías, Victor Manuel (Anales de Psicología / Annals of Psychology, 2006)
The phenomena of memory fluctuations plus two incremental memory effects, hypermnesia and reminiscence were explored for the first time using a paired associates (PAS) paradigm. Fifteen PAS were pre-sented without specific encoding instructions; their recall was tested twice. The main results show: (1) Insignificant levels of between trial fluctua-tions. (2) No sign of hypermnesia. (3) In spite of the previous results, however, highly significant reminiscence. These results are interpreted in terms of the alternative retrieval pathways hypothesis (ARP; Kazén y Solís-Macías, 1999; Solís-Macías, 1998). ARP suggests that hypermnesia emerges due to the activation of such alternative retrieval pathways; that activation transforms a proportion of the available information registered in memory into an accessible form. Using PAS rigidly limited access to al-ternative retrieval pathways, hence hypermnesia was not observed al-though reminiscence did occur. These results reveal some boundary con-ditions for generating hypermnesia.